Characteristics and geological significance of early carboniferous soft-sediment deformation structures in the Kushanhe section, southwest Tarim Basin, Northwest China - Wang, Yijun; Yang, Guang; Wang, Zhenyu; Luo, Shunshe (Frontiers in Earth Science, 2024)
The early Carboniferous Kushanhe Formation and Hantiereke Formation in the Kushanhe section in the piedmont of the southwestern margin of Tarim Basin are in a medium-deep water sedimentary environment with a stratigraphic thickness of more than 500 m, and the sedimentary facies is slope-shelf facies. Among these deposits, soft-sediment deformation structures (SSDS) are common, dominated by various types of slumps. The appearance of SSDS is related to the geotectonic environment of early Carboniferous in southwest Tarim Basin. In the Early Carboniferous, the Paleo-Tethys ocean dived under the Tarim plate, forming a back-arc structure, and a structural slope break belt easily appeared along the basin edge, which provided topographic conditions for the development of marginal platform marginal belt and slope facies. Under this background, the ultra-thick volcanic rocks of Wulate Formation accumulate along the subduction zone, and earthquakes with M≥ 5.0 are prone to occur. Landslides related to earthquakes and corresponding SSDS are easily triggered at the outer edge of the slope break zone. The large earthquake induced by tectonic environment is an important trigger factor of early Carboniferous SSDS. Therefore, the appearance of early carboniferous SSDS in Kushanhe section is an important sedimentary response to the early carboniferous piedmont tectonic activities in southwestern Tarim.